Utilizing a chromosomal-length genome assembly to annotate the Wnt signaling pathway in the Asian citrus psyllid, Diaphorina citri - Chad Vosburg (GigaScience Press, 2021)
The Asian citrus psyllid, Diaphorina citri, is an insect vector that transmits Candidatus Liberibacter asiaticus, the causal agent of the Huanglongbing (HLB), or citrus greening disease. This disease has devastated Florida’s citrus industry, and threatens California’s industry as well as other citrus producing regions around the world. To find novel solutions to the disease, a better understanding of the vector is needed. The D. citri genome has been used to identify and characterize genes involved in Wnt signaling pathways. Wnt signaling is utilized for many important biological processes in metazoans, such as patterning and tissue generation. Curation based on RNA sequencing data and sequence homology confirms 24 Wnt signaling genes within the D. citri genome, including homologs for beta-catenin, Frizzled receptors, and seven Wnt-ligands. Through phylogenetic analysis, we classify D. citri Wnt ligands as Wg/Wnt1, Wnt5, Wnt6, Wnt7, Wnt10, Wnt11, and WntA. The D. citri version 3.0 genome with chromosomal length scaffolds reveals a conserved Wnt1-Wnt6-Wnt10 gene cluster with a gene configuration like that in Drosophila melanogaster. These findings provide greater insight into the evolutionary history of D. citri and Wnt signaling in this important hemipteran vector. Manual annotation was essential for identifying high quality gene models. These gene models can be used to develop molecular systems, such as CRISPR and RNAi, which target and control psyllid populations to manage the spread of HLB. Manual annotation of Wnt signaling pathways was done as part of a collaborative community annotation project.